2019
DOI: 10.3390/cancers11111786
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Inducers of Apoptosis in Ovarian Cancer

Abstract: Ovarian cancers remain one of the most common causes of gynecologic cancer-related death in women worldwide. The standard treatment comprises platinum-based chemotherapy, and most tumors develop resistance to therapeutic drugs. One mechanism of developing drug resistance is alterations of molecules involved in apoptosis, ultimately assisting in the cells’ capability to evade death. Thus, there is a need to focus on identifying potential drugs that restore apoptosis in cancer cells. Here, we discuss the major i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 203 publications
(239 reference statements)
2
49
0
Order By: Relevance
“…The ratio of BCL-2/BAX determines the fate of cells. Overexpression of BCL2 inhibits cell apoptosis, leads to resistance to cisplatin, and results in the poor prognosis of cancer patients [43]. In the current study, the treatment of ovarian and endometrial cancer cells with DDP and progesterone-calcitriol combination significantly decreased the BCL2.…”
Section: Discussionsupporting
confidence: 50%
“…The ratio of BCL-2/BAX determines the fate of cells. Overexpression of BCL2 inhibits cell apoptosis, leads to resistance to cisplatin, and results in the poor prognosis of cancer patients [43]. In the current study, the treatment of ovarian and endometrial cancer cells with DDP and progesterone-calcitriol combination significantly decreased the BCL2.…”
Section: Discussionsupporting
confidence: 50%
“…The red lines denoted the activity restricted by UDCA. especially the expression of several members of the Bcl-2 family (Binju et al, 2019). The nuclear fraction of Nrf2 is able to bind to the Bcl-2 promoter and activate an anti-apoptotic program (Gupta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As(III) exposure stimulated excessive ROS generation, which seems to play a critical role in promotion the activity of p53 pathway ( Sena and Chandel, 2012 ; Alamolhodaei et al., 2015 ). p53 is a tumor suppressor protein that promotes the apoptotic process ( Jiang and Rusling, 2019 ; Silva-Adaya et al., 2020 ) and directly regulate the activity of the pro-apoptotic protein Bax, which further facilitates mitochondrial membrane permeabilization and apoptosis, especially the expression of several members of the Bcl-2 family ( Binju et al., 2019 ). The nuclear fraction of Nrf2 is able to bind to the Bcl-2 promoter and activate an anti-apoptotic program ( Gupta et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, although Bcl-2 pro-survival proteins can prolong the survival period of tumor cells in hematological tumors, playing an important role in tumori-genesis ( 54 ), the truth seems to be opposite in ovarian cancer cell lines. Although the expression of Bcl-2 family proteins in ovarian cancer cells and tissues has not yet been fully elucidated, studies have confirmed that Bcl-2 family proteins play a key role in ovarian cancer chemotherapy ( 56 , 57 ). Bcl-2 pro-survival proteins are listed below:…”
Section: Bcl-2 Family Members In Ovarian Cancermentioning
confidence: 99%